Exosomal circ_0088300 Derived From Cancer-Associated Fibroblasts Acts as a miR-1305 Sponge and Promotes Gastric Carcinoma Cell Tumorigenesis - Shi, Hao; Huang, Shan; Qin, Mingde; Xue, Xiaofeng; Guo, Xingpo; Jiang, Linhua; Hong, Han; Fang, Jian; Gao, Ling (Frontiers in Cell and Developmental Biology, 2021)
Cancer-associated fibroblast (CAF)-derived exosomes play a major role in gastric carcinoma (GC) tumorigenesis. However, the mechanism behind the activity of circular RNAs in CAF-derived exosomes in GC remains unclear. In the present study, we identified differentially expressed circ_0088300 in GC tissues and plasma exosomes. We found that CAFs delivered functional circ_0088300 to GC tumor cells via exosomes and promoted the proliferation, migration and invasion abilities of GC cells. Furthermore, we demonstrated that circ_0088300 packaging into exosomes was driven by KHDRBS3. In addition, we verified that circ_0088300 served as a sponge that directly targeted miR-1305 and promoted GC cell proliferation, migration and invasion. Finally, the JAK/STAT signaling pathway was found to be involved in the circ_0088300/miR-1305 axis, which accelerates GC tumorigenesis. In conclusion, our results indicated a previously unknown regulatory pathway in which exosomal circ_0088300 derived from CAFs acts as a sponge of miR-1305 and promotes GC cell proliferation, migration and invasion; these data identify a potential biomarker and novel therapeutic target for GC in the future.